Characteristics of the Course of Hymenolepidosis and Askaridosis in Children (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article presents the results of the observation of 64 children with intestinal parasitosis, from 3 to 14 years old. The diagnosis of hymenolepidosis and giardiasis was confirmed by the detection of cysts and vegetative forms of giardia and Hymenolepis nana eggs with triple coproscopy; in some cases, giardiasis was diagnosed when trophozoites were detected in duodenal contents. The diagnosis of hymenolepidosis was confirmed by the detection of helminth eggs in freshly excreted feces. The diagnosis of giardiasis was confirmed by the detection of giardia cysts with coproscopy.